2022
DOI: 10.3390/jcm11102938
|View full text |Cite
|
Sign up to set email alerts
|

Do Oral Pathogens Inhabit the Eye and Play a Role in Ocular Diseases?

Abstract: Fascinatingly, the immune-privileged healthy eye has a small unique population of microbiota. The human microbiome project led to continuing interest in the ocular microbiome. Typically, ocular microflorae are commensals of low diversity that colonize the external and internal sites of the eye, without instigating any disorders. Ocular commensals modulate immunity and optimally regulate host defense against pathogenic invasion, both on the ocular surface and neuroretina. Yet, any alteration in this symbiotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 158 publications
(179 reference statements)
0
3
0
Order By: Relevance
“…Low levels of oral Lactococcus also imply that microbial dysbiosis plays a part in the pathogenesis of GM [85]. The significantly higher oral bacterial load observed in GM patients revealed that constant exposure to bacterial products in GM patients exacerbates the severity/progression of the disease [162].…”
Section: Gmmentioning
confidence: 99%
“…Low levels of oral Lactococcus also imply that microbial dysbiosis plays a part in the pathogenesis of GM [85]. The significantly higher oral bacterial load observed in GM patients revealed that constant exposure to bacterial products in GM patients exacerbates the severity/progression of the disease [162].…”
Section: Gmmentioning
confidence: 99%
“…A "core" microbiota, consisting of a few taxa, is shared among all individuals [20], encompassing commensal, environmental, and potentially pathogenic bacteria [21]. The predominant phyla observed on the OS include Proteobacteria, Actinobacteria, and Firmicutes [11,12,22,23,24,25,26,27,28]. At the genus level, commonly found taxa comprise Pseudomonas, Propionibacterium, Bradyrhizobium, Corynebacterium, Acinetobacter, Brevundimonas, Staphylococci, Aquabacterium, Sphingomonas, Streptococcus, Streptophyta, and Methylobacterium.…”
Section: Introductionmentioning
confidence: 99%
“…Detecting the specific aetiological agent, as well as understanding the ocular microbiota and its relationship with the host and the patient's comorbidities, allows for optimal management of these infections [10][11][12]. Gram-positive bacteria are the main contributors to bacterial eye infections, such as Staphylococcus aureus and coagulase-negative Staphylococcus, where some species belonging to the skin microbiota are found, e.g., S. epidermidis and S. saprophyticus [13,14].…”
Section: Introductionmentioning
confidence: 99%